NEW VALIDATED METHOD FOR THE ESTIMATION OF ALLANTOIN AND PERMETHRIN USIGN RP-HPLC IN BULK AND PHARMACEUTICAL DOSAGE FORM - S., MADHAVI; REDDY, CHALLA SUDHEER; RAO, B. TIRUMALESWARA (International Journal of Applied Pharmaceutics, 2021)
Objective: Special, effective high pressure liquid chromatography method has been developed for the simultaneous quantification of Allantoin and Permethrin. Methods: By using Waters HPLC e-2695 quaternary pump with a PDA detector of 2998 instrument the chromatographic separation of Allantoin and Permethrin was achieved on the column of Symmetry C18 (150x4.6 mm, 3.5 µm) using an isocratic elution with a buffer containing 0.1percent ortho phosphoric acid and acetonitrile at a rate of 40:60 as a mobile phase with a flow rate of 1 ml/min at ambient temperature. A detector wavelength of 226 nm utilizing the PDA detector were given in the instrumental settings. The linearity was studied between the concentration range of 1-15 µg/ml of Allantoin and 25-375 µg/ml of Permethrin were injected with a run time of 6 min. As a part of method validation the parameters like specificity, linearity, accuracy, ruggedness, robustness were determined and the results were found to be within the allowable limit. Validation of the proposed method was carried out according to an International Conference on Harmonization (ICH) guidelines. Results: LOD and LOQ for the two active ingredients were established with respect to test concentration. The plotted calibration curves were linear with a regression coefficient of R2>0.999, indicates that the linearity was with in the limit. As a part of method validation the parameters like specificity, linearity, accuracy, ruggedness, robustness were determined and the results were found to be within the allowable limit. Conclusion: The method developed was found to be applicable to routine analysis and to be used for the measurement of both active pharmaceutical ingredients (i. e, Allantoin and Permethrin). Since, there is no HPLC method reported in the literature for the estimation of Allantoin and Permethrin, there is a need to develop quantitative methods under different conditions to achieve improvement in specificity, selecivity etc.